2017
DOI: 10.1016/j.socscimed.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Correlational study and randomised controlled trial for understanding and changing red meat consumption: The role of eating identities

Abstract: Rationale: The present studies aimed to contribute to the literature on psychological variables involved in reducing red meat consumption (RMC).Objective: Study 1 investigated whether the theory of planned behaviour (TPB), plus healthy-eating and meat-eating identities, could explain intentions to reduce RMC. Study 2 evaluated the effectiveness of an SMS intervention on self-monitoring to reduce RMC.Methods: In Study 1, data were collected daily using online food diaries for one week and a TPB questionnaire. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 71 publications
6
83
0
3
Order By: Relevance
“…Past experimental studies of meat reduction are scarce, and those that use a comparable meat consumption measure are even scarcer. Nevertheless, the degree of change over time in the present study resembles that from one previous study, which found a reduction of about 1.5 portions of red meat per week (Carfora et al, 2017). Similarly, the reduction in GHG in the present study is equivalent to approximately one less portion of red meat (i.e., pork) per week for the average participant, or two portions for participants in the group-matched condition.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Past experimental studies of meat reduction are scarce, and those that use a comparable meat consumption measure are even scarcer. Nevertheless, the degree of change over time in the present study resembles that from one previous study, which found a reduction of about 1.5 portions of red meat per week (Carfora et al, 2017). Similarly, the reduction in GHG in the present study is equivalent to approximately one less portion of red meat (i.e., pork) per week for the average participant, or two portions for participants in the group-matched condition.…”
Section: Discussionsupporting
confidence: 84%
“…Other experimental studies focused on self-regulation techniques. Individuals who received information about the maximum weekly recommended intake of red meat and daily texts reminders to self-monitor their servings significantly reduced their consumption of red meat, compared to that of a control group (Carfora, Caso, & Conner, 2017). In a different study, individuals in an implementation-intention condition reported larger reductions in meat consumption than those in an information-only condition (Loy et al, 2016).…”
Section: Meat Reduction Experimentsmentioning
confidence: 84%
See 1 more Smart Citation
“…Another field experiment on college cafeteria choices found experimental evidence that an intervention that doubled the availability of vegetarian choices, from 25% to 50% of total offerings, increased vegetarian dish selection by 7.8 percentage points, from 19.1% to 26.9% [23]. While these interventions demonstrate effects that are similar or slightly larger in size than those we would anticipate from restaurant menu messaging, they require significantly greater operational costs, effort, and accommodation, such as repeated daily contact [22], calculating the carbon footprint of all dishes offered and updating this information as new dishes are introduced [21], or making extensive changes to offerings [23].…”
Section: Introductionmentioning
confidence: 94%
“…One study, implemented in a student catering facility, found that providing information about the carbon footprint of various food choices resulted in a 4.8 percentage point reduction in meat dishes labeled with high emissions-but an 11.5 percentage point increase in meat dishes labeled as having low emissions-leading to an estimated 3.6 percentage point reduction in emissions [21]. In another study, researchers sent daily text messages to undergraduate college students to reduce their red meat consumption, and found a self-reported reduction of roughly 1.5 portions of red meat over the course of a week, but did not assess objective measures or if other meat was substituted for red meat [22]. Another field experiment on college cafeteria choices found experimental evidence that an intervention that doubled the availability of vegetarian choices, from 25% to 50% of total offerings, increased vegetarian dish selection by 7.8 percentage points, from 19.1% to 26.9% [23].…”
Section: Introductionmentioning
confidence: 99%